Evaluasi Penerapan Software Akuntansi Accurate dalam Penyusunan Laporan Laba Rugi - Hasni Aropah; Eko Setyanto (Pusat Riset dan Inovasi Nasional, 2024)
Accurate accounting software is a business application that helps SMEs manage their business easily. Processing financial data into financial reports needed to help plan the company's future. The profit and loss report is a financial report that reports on the company's operational activities by calculating income and expenses for one period and then the profit and loss report can be determined. The profit and loss report can be used as a way to assess the company's level of success in a certain period and also to understand the company's development. This research aims to determine the evaluation of the application of accurate accounting software in preparing profit and loss reports. The type of research used is qualitative research, with a sampling technique, purposive sampling. The research method used is User Acceptance Testing, with a type of testing, Black Box Testing. The results of this research show that accurate accounting software is effective in preparing profit and loss reports, easy to understand and easy to detect errors. This error can be detected by reviewing the transaction data that has been input. With the help of Standard Operating Procedures, companies can minimize errors, make control easier and enable to run company smoothly